GENETIC VARIATION AND HERITABILITY OF ELEVEN TEA CLONES ON CHARACTERISTIC OF RESISTANCE AGAINST EMPOASCA SPP. - Driska Arnanto (Universitas Sarjanawiyata Tamansiswa, 2021)
Genetic variation and heritability of resistance to Empoasca spp. was studied in ten clones PGL series and TRI 2025. The research conducted in tea research station in Pagilaran, Batang, Central Java and in the laboratory of Food Chemistry and Nutrition Faculty of Agricultural Technology, LPPT UGM and Genetic Laboratory Faculty of Agricultural, Gadjah Mada University. This research used randomly complete block design of ten clones PGL and TRI 2025 with four blocks as replications. The damage intensity and morphological anatomy data each clone PGL series and TRI 2025 were observed. Analysis of biochemical (tannins content and peroxidase enzyme acitivity) using the spectrophotometric method. Data were analyzed using ANOVA and heritability. The result shows that has high estimated heritability value in damage intensity, hair leaf density, enzym peroxide activity, tannin content, stomata density, and epidermis thickness (abaxial and adaxial). Cluster analysis based on morphological anatomy divide into four group and resistant clone against Empoasca spp. consisted of four category, based on principal component analysis.